Remediation of oil contaminated media using organic material supplementation - Dadrasnia, A.; Salmah, I.; Emenike, C.U.; Shahsavari, N. (Marcel Dekker (now owned by Taylor & Francis), 2015)
With the fact that anthropogenic activities are inevitable, especially with the continuous use of fossil fuels and other sources of hydrocarbons, environmental pollution appears to be a recurring issue. However, nascent science and technologies try to identify and apply varied options that can remedy polluted sites, which include oil spill situations. The present review elucidates the remediation options on the event of oil spill/contamination with emphasis on the adoption of biological treatment (supplement addition and phytoremediation), and overview on the potential relevance of remediation via advances in nanotechnology. The associated negativities and cost tend to outweigh the advantages of both methods when sustainability is considered.